Sustainability in community archaeology - Paul Belford (AP, 2017)
This paper considers the rise of community archaeology in England and Wales, its relationships with other branches of archaeology, and its longterm sustainability. Possible meanings of sustainability are discussed from an international and interdisciplinary perspective, before questions of social, intellectual and economic sustainability in community archaeology are considered. It is argued that true sustainability for community archaeology will only be possible if research outcomes and public benefit are considered as being of equal value.